2018
DOI: 10.1111/jce.13485
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic pulmonary vein isolation during isthmus ablation for atrial flutter: Three‐year outcomes of the PREVENT AF I study

Abstract: Prophylactic PVI in patients with only typical AFL resulted in a significant reduction of new-onset AF and burden during long-term follow-up as assessed by ICM, with consequent reduction in hospitalizations and need to perform repeat ablation for AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…A separate analysis was performed to determine the effect of the combined procedure at 2 years. Long‐term outcomes of the PREVENT AF study were recently published, and these data were used for the 2‐year analysis. CTI alone was associated with nearly a 2‐fold increase risk of recurrent AA at 2 years (1.94 [1.16, 3.23] 95% CI, P = 0.01, Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A separate analysis was performed to determine the effect of the combined procedure at 2 years. Long‐term outcomes of the PREVENT AF study were recently published, and these data were used for the 2‐year analysis. CTI alone was associated with nearly a 2‐fold increase risk of recurrent AA at 2 years (1.94 [1.16, 3.23] 95% CI, P = 0.01, Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, there was a difference in the proportion of patients developing AA between years 1 and 2. Data from the two studies reporting a minimum 2‐year follow‐up, revealed that 18.8% of patients in the CTI plus PVI group developed AF between years 1 and 2, compared to 11.3% in the CTI‐only group. This may represent a proarrhythmic effect of PVI with development of left atrial macroreentrant atrial tachycardias associated with the ablation procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These issues are explored in an important study in this issue of the journal by Romanov et al . These investigators present the 3‐year outcomes of the PREVENT AF I Study, which enrolled patients with typical cavotricuspid isthmus (CTI)‐dependent atrial flutter (AFL), without any prior history of atrial fibrillation (AF).…”
mentioning
confidence: 98%